Catalytic enantioselective intermolecular cycloadditions of a 2-diazo-3,6-diketoester-derived carbonyl ylide with alkyne and strained alkene dipolarophiles - Hodgson, D; Labande, A; Glen, R; Redgrave, A (2003)
Catalytic enantioselective tandem carbonyl ylide formation-cycloaddition reactions of tert-butyl 2-diazo-3,6-dioxoheptanoate 7 with alkyne and strained alkene dipolarophiles to afford the corresponding cycloadducts with up to 92% ee are described. © 2003 Elsevier Science Ltd. All rights reserved.